Psychopathic traits affect the visual exploration of facial expressions - Boll, Sabrina; Gamer, Matthias (Biological psychology, 2016)
Deficits in emotional reactivity and recognition have been reported in psychopathy. Impaired attention to the eyes along with amygdala malfunctions may underlie these problems. Here, we investigated how different facets of psychopathy modulate the visual exploration of facial expressions by assessing personality traits in a sample of healthy young adults using an eye-tracking based face perception task. Fearless Dominance (the interpersonal-emotional facet of psychopathy) and Coldheartedness scores predicted reduced face exploration consistent with findings on lowered emotional reactivity in psychopathy. Moreover, participants high on the social deviance facet of psychopathy (‘Self-Centered Impulsivity’) showed a reduced bias to shift attention towards the eyes. Our data suggest that facets of psychopathy modulate face processing in healthy individuals and reveal possible attentional mechanisms which might be responsible for the severe impairments of social perception and behavior observed in psychopathy.